Impediments for experimentation in novice design teams. Issue 3 (2nd October 2018) - Rekonen, Satu; Hassi, Lotta
Abstract: Despite the increasing interest in design thinking, there still is a lack of empirical understanding on what happens when design thinking, or elements of it, are adopted in organizations not accustomed to such approaches. Experimentation is one of the fundamentals of design thinking, and this study explores the impediments for experimentation in four novice design teams taking part in short-term experimentation sprints in a Finnish financial organization. This study adopted a case-study and action research approach and data was gathered through video-recoding and semi-structured interviews. Four central themes that may become bottlenecks when aiming to adopt experimentation in novice teams were identified: resistance to iteration, overlooking the experimentation ideas of others' and oneself, losing sight of the initial problem to be solved, and a bias towards planning. The study showed that adopting experimentation, in novice design teams requires the team to adopt an appropriate mindset that is open for modifications in the idea and for iteration in the experimentation cycle.